A 7-year retrospective study: comparison of the efficacy between rotational osteotomy at the base of femoral neck and vascularized iliac bone flap transfer in the treatment of osteonecrosis of the femoral head - Xia, Tianwei; Sun, Jiahao; Wang, Lu; Zheng, Shanbin; Li, Yukun; Li, Muzhe; Zhang, Tianchen; Hu, Tianjie; Shen, Jirong; Ma, Yong (Frontiers in Surgery, 2025)
ObjectiveTo compare the clinical efficacy of rotational osteotomy at the base of femoral neck and iliac bone flap transfer with ascending branch of lateral femoral circumflex artery(vascularized iliac bone flap transfer) in the treatment of ARCO III stage, CJFH-L type osteonecrosis of femoral head.MethodsWe compared 25 cases (Group A), in which 25 hips underwent rotational osteotomy at the base of femoral neck and 25 cases (Group B), in which 25 hips underwent vascularized iliac bone flap transfer in our hospital from September 2017 to March 2024.The operative time and hospitalization time were compared, the collapse and repair of femoral head and the healing of osteotomy were evaluated, and the reasons of failure were analyzed.ResultsAll operations were conducted successfully in both groups. The follow-up time was 36.2 ± 21.62 months. The operation time in Group A was (215.20 ± 56.80) minutes, which was longer than that in Group B (183.96 ± 32.14) minutes (P = 0.022). There was significant difference in the hospitalization time between the two groups. There was no significant difference in Harris scores between Group A and group B before operation (P = 0.831). However, there was significant difference in Harris scores after 3 months, 6 months and at the last follow-up (all P < 0.05) in Group A and Group B. The excellent and good rate of Group A was 36% (9 hips), the good rate of Group B was 44% (11 hips). During the longest 7-year follow-up period, 6 hips in Group A and 4 hips in Group B underwent arthroplasty. In addition, one hip in group A underwent total hip exclusion because of infection. DCE-MRI showed that abnormal hyperperfusion of the repaired area was alleviated, and the blood supply of the necrotic area was restored.ConclusionBoth rotational osteotomy of the base of the femoral neck under surgical dislocation and vascularized iliac bone flap transfer can obtain satisfactory short-term results in the treatment of CJFH-L type, ARCO III stage osteonecrosis of the femoral head. Rotational osteotomy at the base of femoral neck under surgical dislocation can be chosen to delay the collapse process for CJFH-L2 type, ARCOⅢB stage ONFH. Vascularized iliac bone flap transfer has the advantage of short operation time. It is easier and suitable for CJFH-L1 type, ARCOⅢA stage ONFH.